IMPLEMENTASI PERSPEKTIF PEMBELAJARAN DAN PERTUMBUHAN, PROSES BISNIS INTERNAL DAN PELANGGAN DALAM PERENCANAAN STRATEGIS ( Studi kasus pada Badan Amil Zakat Daerah /BAZDA Kabupaten Banyumas) - Dwita Darmawati; Utami Puji Lestari; Umi Widyastuti (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2006)
This research is a study case on Badan Amil Zakat Daerah (BAZDA) Kabupaten Banyumas. It’s purpuse is to explore and to analyze BAZDA’s management based on Balanced Sroecard with three perspectives namely customer, internal bussines Procces, learning and growth. Data were collected using interview with BAZDA managers and literature study about BAZDA annual reports.This research shown that BAZDA only use annual panning in performing it’s activities and has not use strategic planning yet. Contribution of this research is strategic planning prototype for BAZDA Kabupaten Banyumas in Balanced Scorecard frame.